Cardiovascular Endurance Level of Futsal Players - Muhammad Ishak; Hikmad Hakim; Andi Ridwan; Arman Fadillah (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
The study aims to determine the level of Cardiovascular Endurance of Extracurricular Futsal. This type of research is descriptive research. The population in this study were Futsal Players of SMAN 4 Pangkep with a sample size of 20 students and sampling using purposive sampling where the sampling technique was based on consideration. To obtain data, researchers used the Multi Stage Fitness Test (Bleep Test), from the results of the study 3 people had poor cardiovascular endurance (15%), 6 people had moderate cardiovascular endurance (30%) and 10 people had good endurance (50%) and 1 person had very good endurance (5%). In general, the level of cardiovascular endurance conditions of students at SMAN 4 Pankep is predominantly categorized as Good. The suggestions given are: 1) Futsal extracurricular members are advised to increase their cardiovascular endurance to support physical abilities that will affect increased achievement, and 2) Coaches are advised to provide various cardiovascular endurance training and physical components that support Futsal in particular and various sports in general.